Inqādz al-Naz’ah al-Insāniyyah fī al-Khitāb al-Kalāmi al-Jadīd: Qirā’ah fī Shūrat al-Insāniyyah al-Imāniyyah wa al-Akhlāqiyyah fī Fikr ‘Abd al-Jabbār Rifā’i - Fahmi, Ahmad Lukman; Menad, Safia (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This article examines the issue of humanism in the new kalām discourse, which has been discussed by ‘Abd Al-Jabbar Al-Rifai in most of his writings, he has started from a critical review of the kalām-tauhidī paradigm that affects the production of religious knowledge and is only oriented towards proving and defending religious beliefs. This article shows that the orientation of the new kalām is to reveal the beauty of religion and highlight its human values. The meaning of humanism that al-Rifai has discussed, which he calls faith-based humanism, is different from the concept of humanism developed in the Western context. This article aims to present and discuss the issue of humanist values in the new kalām discourse, especially from the perspective of al-Rifai as its most important theorist. The research has used an analytical descriptive approach, collecting data and information obtained from Al-Rifai's books related to the subject matter. This article has reached several conclusions, the most important of which are, first, that the relationship between humans and their God in classical kalām discourse is based on fear and slave psychology, according to Al-Rifai this kind of relationship can lead to what he calls the theology of slavery, he then tries to present a new relationship based on a concept where human attitudes are more positive interactions based on love.. Secondly, an important methodology in uncovering humanist values from religious texts according to Al-Rifai will not succeed except by critically reviewing the history of religious thought, reading critical analysis of religious texts, and presenting turāts from different perspectives and visions, such as reading and re-understanding the names and attributes of God, not in the traditional way, but in a humanitarian-oriented way